A Dynamic Approach to the Theory of Consumer Demand - Cramer, J. S. (Review of Economic Studies, 1957)
Journal Article A Dynamic Approach to the Theory of Consumer Demand Get access J. S. Cramer J. S. Cramer Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 2, February 1957, Pages 73–86, https://doi.org/10.2307/2295761 Published: 01 February 1957